Ta’limul Muta’allim: Strategi Lembaga Pendidikan dalam Membentuk Sikap Profesionalisme Guru Pendidikan Agama Islam (PAI) - Nurmawati Nurmawati; Nadia Ainin; Muhammad Jafar; Ghisena Aghisni (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2025)
This research was motivated by many immoral cases that occurred in the pesantren environment. It is a terrible moral disaster in the world of education, where institutions oriented towards Islamic education should give birth to Islamic characters, but in reality, the bearers of education are the main actors in moral depravity. The purpose of this study is to thoroughly explore the ideal characteristics of an educator according to Syaikh Az-Zarnuji in the book Ta'limul Muta'allim and how the institution's strategy in shaping the professionalism of PAI teachers. The result of this study is that there are 6 characters that a teacher must have: 1) Knowledgeable 2) Mature personality (wara') 3) Charismatic 4) Mature 5) Generous 6) Merciful and patient. These six characters are very relevant to the aspects of education, especially PAI teachers who do not only prioritize knowledge. However, knowledge must be accompanied by the formation of learner character and interactive learning. Thus, the institution can take the main role in shaping the professionalism of PAI teachers so as to realize the true purpose of Islamic religious education.